2014
DOI: 10.22452/jscp/vol5no1.5
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Sustainability Principles of Building: Formulation of a Theoretical Framework

Abstract: Sustainable development has received encouraging attention since the Rio Declaration on Environment and Development was signed in 1992 Earth Summit. In Malaysia, the focus on sustainability in building, especially in devising policies has been spelled out in the government policies at national, state and local level. It can be considered that many efforts relating to sustainability in building project have been implemented in the country, however till now sustainability in Malaysian building projects are still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Overcoming resistance to change and transitioning to more advanced sustainability-oriented methods are crucial steps to be taken. Financial Financial challenges, including the perception that sustainable construction is costlier, contribute to the reluctance of developers to adopt sustainable practices (Isa Kalsum et al, 2014). Addressing these economic factors and integrating life-cycle costs into project evaluations can help promote the implementation of sustainable construction.…”
Section: Passive Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Overcoming resistance to change and transitioning to more advanced sustainability-oriented methods are crucial steps to be taken. Financial Financial challenges, including the perception that sustainable construction is costlier, contribute to the reluctance of developers to adopt sustainable practices (Isa Kalsum et al, 2014). Addressing these economic factors and integrating life-cycle costs into project evaluations can help promote the implementation of sustainable construction.…”
Section: Passive Culturementioning
confidence: 99%
“…Client demand and willingness are among the most important drivers for promoting sustainable construction practices implementation. The economic factor was found to have a minimal impact on sustainable construction understanding (Benson et al, 2017;Isa Kalsum et al, 2014;Lélé, 2018). Providing economic incentives can encourage the adoption and implementation of sustainable practices (Adepoju & Aigbavboa, 2020;Saleh & Alalouch, 2015) and address concerns about high initial investments.…”
Section: : Measurement Model Of Sustainable Construction Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, sustainability all over the whole life cycle shall take into account carefully selected building materials and robust solutions so risk and costs associated with cleaning, maintenance and recyclability are reduced. In a more scientific literature, Berardi (2013) clarified the new interpretations of the concept of sustainable buildings; Isa et al (2014) presented a review on sustainability principles of buildings; and Park and Nagy (2018) stated that balancing the reduction of the energy demands (through optimal building operation) with thermal comfort, is required for a sustainable and comfortable building stock. Still, focussed on the topic of comfort in buildings, Barbosa et al (2016) investigated vulnerability factors that influence thermal comfort in the context of climate change, as well as variability and adaptive strategies that could be adopted; Saraiva et al (2018) addressed the importance of using indicators related to environmental comfort in sustainability assessment tools applied to school buildings; and Pomfret and Hashemia (2017) evaluated thermal comfort in domestic zero energy buildings.…”
Section: Strands Covered By Technical Management Of Buildingsmentioning
confidence: 99%
“…Early efforts were proposed to achieve sustainability within three domains described as environment, social, and economy. These three domains are known as the triple bottom line (Nahmens and Ikuma, 2012;Isa, Samad and Alias, 2014). Accordingly, an abundance of research efforts since 1990 can be found on how to make construction as sustainable as possible.…”
Section: Introductionmentioning
confidence: 99%